2020
DOI: 10.1016/j.ijhydene.2020.04.122
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of novel NGCO-LSCF composite cathode for intermediate temperature solid oxide fuel cells

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…[100] Likewise, increase in surface oxygen exchange kinetics and expansion of electrochemical reaction zone in the LSCF-GCO composite can be achieved by incorporating GCO to A-site deficient LSCF material. [101] As reported in different studies, the observed variation in polarization resistance can be linked to the size and configuration of LSCF when different amounts of GCO are introduced. [102,103] Figure 13 shows SEM images of LSCF-GCO cathodes with different compositions.…”
Section: Lscf (La 1-x Sr X Co 1-y Fe Y O 3-δ ) Cathode Materialsmentioning
confidence: 83%
“…[100] Likewise, increase in surface oxygen exchange kinetics and expansion of electrochemical reaction zone in the LSCF-GCO composite can be achieved by incorporating GCO to A-site deficient LSCF material. [101] As reported in different studies, the observed variation in polarization resistance can be linked to the size and configuration of LSCF when different amounts of GCO are introduced. [102,103] Figure 13 shows SEM images of LSCF-GCO cathodes with different compositions.…”
Section: Lscf (La 1-x Sr X Co 1-y Fe Y O 3-δ ) Cathode Materialsmentioning
confidence: 83%
“…The thermal decomposition behavior analysis of the LSCF-ZnO was conducted using a TGA zanalyzer model Pelkin Elmer STA 600®, from 30 o C to 800 o C with a heating rate of 5 o C/min in air and air flowrate of 50 cm 3 /min. For calcined composited cathode powder, the value of oxygen stoichiometric was calculated via equation 1 (Samreen et al, 2020). 𝛥𝑚/𝑚 𝑠 refers to weight loss of the material, Msample represent the molecular weight of the sample, Moxygen refers to molecular weight of oxygen.…”
Section: Characterization Proceduresmentioning
confidence: 99%
“…The thermal decomposition behaviour of LSCF-NiO was investigated using a TGA analyser model Pelkin Elmer STA 600 ® from room temperature to 900 • C with an air flow rate of 50 cm 3 /min and a heating rate of 5 • C/min in air. The oxygen stoichiometric value of calcined composited cathode powder was calculated using Equation (2) [24]. ∆m/m s refers to weight loss of the material, M sample represent the molecular weight of the sample, M oxygen refers to molecular weight of oxygen.…”
Section: Characterizationmentioning
confidence: 99%
“…The study was conducted at temperatures ranging from room temperature to 800 • C to simulate the oxygen filling and emptying capabilities of the device when utilized at an intermediate temperature range [28,29]. According to the graph's trend between 30 and 300 • C, the weight loss indicated the evacuation of absorbed water from the surrounding environment [24]. A slight weight increase was observed above 300 • C, implying that Co 3+ /Fe 3+ is thermally oxidized to Co 4+ /Fe 4+ .…”
Section: Electrochemical Properties Of the Symmetrical Composite Cath...mentioning
confidence: 99%